Early reproduction onset in four species of Didelphimorphia in the Peruvian Amazonia - Díaz, María Mónica (2008)
Precise data about age of sexual maturity in didelphids are scarce, although knowledge on the reproductive patterns is well known from several publications (TyndaleBiscoe and MacKenzie 1976, Tyndale-Biscoe and Renfree 1987, Harder 1992, McAllan 2003, Monteiro-Filho and Cá ceres 2006). The limited knowledge published on sexual maturity is mainly due to the difficulties in establishing correlations between chronological and dental age; the latter is determined by the sequence of tooth replacement (Astúa and Geise 2006). Some published reports (e.g., Atramentowicz 1986, Gentile et al. 1995, Astúa and Geise 2006) revealed an early onset of the reproductive period in some species of didelphids, where young or subadult specimens (based on tooth replacement) were sexually mature. According to Astúa and Geise (2006), early sexual maturity is a strategy related to the capacity to produce more than one litter during the highest productive season.